2008
DOI: 10.4319/lo.2008.53.5.1862
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 and cobalt cycling among diatoms and bacteria in Antarctic sea ice microbial communities

Abstract: Within McMurdo Sound's annual sea ice, assimilation and concentrations of vitamin B 12 (cobalamin), microbial community productivity, and biomass were examined among three 100-m 2 quadrats where light penetration was manipulated by snow cover during austral summer. From late October through December, B 12 concentrations (6-32 pmol L 21 ) and assimilation rates (17-780 pmol m 22 d 21 ) in congelation ice covaried with primary productivity (0.0001-250 mmol C m 22 d 21 ) and chlorophyll a (0.6-36 mg m 22 ). Withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 57 publications
(94 reference statements)
3
24
0
Order By: Relevance
“…However, the similar dissolved B 12 concentrations measured using the bioassay technique in the open-ocean waters of different marine systems in the 1950s and 1960s (ranging from undetectable to ∼7 pM) along with the levels measured more recently using direct techniques (Table 4) suggest that, at least for vitamin B 12 , the bioassays and the direct quantifications produce similar results. The same applies to B 12 measurements in the Antarctic, where bioassay-based measurements of dissolved B 12 concentrations (ranging from 0.5 to 2.4 pM; Carlucci & Cuhel 1977, Taylor & Sullivan 2008 were similar to those measured with the direct technique (ranging from 0.5 to 3.5 pM; Panzeca et al 2009). The similar range of concentrations as well as the similar depth profiles obtained by the two methodologies (Figure 5a) in water samples collected in the Pacific Ocean almost 50 years apart suggest that both techniques produce coherent results.…”
Section: The Oceanography Of B Vitaminsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the similar dissolved B 12 concentrations measured using the bioassay technique in the open-ocean waters of different marine systems in the 1950s and 1960s (ranging from undetectable to ∼7 pM) along with the levels measured more recently using direct techniques (Table 4) suggest that, at least for vitamin B 12 , the bioassays and the direct quantifications produce similar results. The same applies to B 12 measurements in the Antarctic, where bioassay-based measurements of dissolved B 12 concentrations (ranging from 0.5 to 2.4 pM; Carlucci & Cuhel 1977, Taylor & Sullivan 2008 were similar to those measured with the direct technique (ranging from 0.5 to 3.5 pM; Panzeca et al 2009). The similar range of concentrations as well as the similar depth profiles obtained by the two methodologies (Figure 5a) in water samples collected in the Pacific Ocean almost 50 years apart suggest that both techniques produce coherent results.…”
Section: The Oceanography Of B Vitaminsmentioning
confidence: 94%
“…In the field, Ohwada & Taga (1972) found that particulate B 1 and B 7 concentrations in surface waters of the North Pacific were approximately 1% of the dissolved concentrations, whereas in coastal waters, particulate B 1 and B 7 concentrations were approximately 150% and 50% of the dissolved concentrations, respectively. The rapid turnover rates calculated for B 12 with respect to biological assimilation (on the order of a few hours; Koch et al 2011, Taylor & Sullivan 2008 suggest that water column vitamin depletion due to biological scavenging is feasible in certain environments.…”
Section: The Oceanography Of B Vitaminsmentioning
confidence: 97%
“…Laboratory cultures of Alphaproteobacteria and Procholorococcus strains had lower amounts of cobalamin or pseudocobalamin (less than 1,200 nmol cobalamin analog per mole carbon) than Synechococcus and Thaumarchaeota isolates (1,480-11,600 nmol cobalamin analog per mole carbon). Published values (17) for sea ice bacterial isolates estimated using a bioassay were highly variable (0.6-6,800 nmol cobalamin analog per mole carbon). In our environmental samples, we observed an average stoichiometry of 87 nmol pseudocobalamin per mole cyanobacterial carbon, lower than the cyanobacterial isolates (Fig.…”
mentioning
confidence: 99%
“…The positive correlation of the cell and ATP data with Al 3+ and K + likely reflect contributions from aeolian transport to the ice 20 surface and subsequent weathering, but the data for Co 2+ (Fig. 3A) are interesting when juxtaposed with the results of Taylor and Sullivan (2008). This study showed that uptake of Co 2+ and vitamin B 12 synthesis by bacteria in Antarctic sea ice supplied this vital micronutrient to algae auxotrophic for B 12 .…”
Section: Discussionmentioning
confidence: 59%